Chronic obstructive pulmonary disease in China: a nationwide prevalence study. Issue 6 (June 2018) - Fang, Liwen; Gao, Pei; Bao, Heling; Tang, Xun; Wang, Baohua; Feng, Yajing; Cong, Shu; Juan, Juan; Fan, Jing; Lu, Ke; Wang, Ning; Hu, Yonghua; et al.
Summary: Background: Because of the rapid change in economic development and lifestyle in China, and the ageing population, concerns have grown that chronic obstructive pulmonary disease (COPD) could become epidemic. An up-to-date nationwide estimation of COPD prevalence in China is needed. Methods: We did a cross-sectional survey of a nationally representative sample of individuals from mainland China aged 40 years or older. The primary outcome was COPD, defined according to the 2017 Global Initiative for Chronic Obstructive Lung Disease (GOLD) lung function criteria. Findings: Between Dec 29, 2014, and Dec 31, 2015, 66 752 adults were recruited to the study population. The estimated standardised prevalence of COPD was 13·6% (95% CI 12·0–15·2). The prevalence of COPD differed significantly between men and women (19·0%, 95% CI 16·9–21·2 vs 8·1%, 6·8–9·3; p<0·0001), mainly because of a significant difference in smoking status between men and women (current smokers 58·2% vs 4·0%). The prevalence of COPD differed by geographic region, with the highest prevalence in southwest China (20·2%, 95% CI 14·7–25·8) and the lowest in central China (10·2%, 8·2–12·2). Among adults with COPD, 56·4% (95% CI 53·7–59·2) had mild disease (GOLD stage I), 36·3% (34·3–38·3) had moderate disease (GOLD stage II), 6·5% (5·5–7·4) had severe disease (GOLD stage III), and 0·9% (0·6–1·1) had very severe disease (GOLD stage IV). Interpretation: In a large, nationally representative sample of adults aged 40 years or older, the estimated overall prevalence of COPD in China in 2014–15 was 13·6%, indicating that this disease has become a major public-health problem. Strategies aimed at prevention and treatment of COPD are needed urgently. Funding: Chinese Central Government, the Ministry of Science and Technology of The People's Republic of China, and the National Natural Science Foundation of China.